1992
DOI: 10.1155/lc.12.211
|View full text |Cite
|
Sign up to set email alerts
|

UV Laser Decay of Oxygen‐Deficient Centers in Silica Glasses

Abstract: Oxygen-deficient centers decay with simultaneous formation of color centers in IR and UV grade silica glasses under KrF laser irradiation was studied. The nonexponential dependence of the ODC photodecay in silica glass on the UV irradiation dose (number of laser pulses) was observed. Postpulse long-time temporal behaviour of recombination luminescence and laser induced photoconductivity was analyzed for the two types of glasses in time scale up to 0.5 ms. Long time fluorescence tail is attributed to migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The increase of light intensity results in an increase of the possibility of multistep processes and subsequent photoionization of ODC5•6 ODC + 2 hv -E' center + e (20) The possibility of this pathway of ODC photoreaction was shown by ESR and UV spectroscopic detection of laser-induced E' centers, by the quadratic dependence of photoreaction yield on laser pulse fluence, and also by direct measurement of photoconductivity in oxygen-deficient silica glasses. 6 In our experiments, the UV pulse energy fluence was ionization of ODC must also be high.6 Figures 6b,c and 7b demonstrate our experimental results on UV laser photochemistry of ODC in hydrogen-saturated silica fibers. The bleaching of the 248 nm ODC absorption band is several times stronger than that for low-intensity irradiation (mercury lamp) with the same dose.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…The increase of light intensity results in an increase of the possibility of multistep processes and subsequent photoionization of ODC5•6 ODC + 2 hv -E' center + e (20) The possibility of this pathway of ODC photoreaction was shown by ESR and UV spectroscopic detection of laser-induced E' centers, by the quadratic dependence of photoreaction yield on laser pulse fluence, and also by direct measurement of photoconductivity in oxygen-deficient silica glasses. 6 In our experiments, the UV pulse energy fluence was ionization of ODC must also be high.6 Figures 6b,c and 7b demonstrate our experimental results on UV laser photochemistry of ODC in hydrogen-saturated silica fibers. The bleaching of the 248 nm ODC absorption band is several times stronger than that for low-intensity irradiation (mercury lamp) with the same dose.…”
Section: Resultssupporting
confidence: 53%
“…The electronic photoexcitation of these ODC gives a strong photoluminescence with maxima at 280-285 nm (singlet-singlet transition) and 450-455 nm (triplet-singlet transition).1 These defect centers can be stabilized both in the bulk and on the surface of silica glasses.2 Irradiation of ODC with UV light initiates reactions which lead to the formation of new types of defects. [3][4][5][6] In previous works,5-8 some important features of these processes stimulated by UV light (both laser and conventional) with different intensities have been shown. The various chemical processes may be used to modify the defect structure of glasses and, thus, to obtain new optical properties.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…To confirm that the observed fluorescence is organic, a subset of the fused silica samples was exposed to repeated laser pulses with the deep ultraviolet (DUV) laser (248.6 nm). Previous work found that exposing fused silica to repeated laser pulses of varying energies can either anneal crystal defects resulting in a decrease of the ∼280 nm feature intensity or increase the concentration of defects, thus increasing the 280 nm feature intensity, depending on laser energy and/or thermal environment (Bagratashvili et al., 1992; Leung et al., 1991; Morgan et al., 2022; Zhou et al., 2014). In this work, repeated laser pulses of several fused silica samples resulted in a decrease of all fluorescence, including the 280/295 nm feature (Figure 4).…”
Section: Discussionmentioning
confidence: 99%